Beef lipids in relation to animal breed and nutrition in Argentina - Garcia, Pilar Teresa; Pensel, Norma Ana; Sancho, Ana Maria; Latimori, Nestor Juan; Kloster, Andres Maria; Amigone, Miguel Angel; Casal, Jorge Jose (Elsevier, 2019)
Fatty acid (FA) composition of intramuscular fat (IMF) in M. Longissimus dorsi (LD) was measured in 72 steers from Angus (A), Charolais × Angus (CHA×A) and Holstein Argentine (HA) breeds. The steers were allotted to four dietary treatments of six animals each: T1, steers grazed on pasture; T2, steers supplemented with cracked corn grain (0.7% of live-weight) daily and free access to pasture; T3, steers supplemented with cracked corn grain (1% of live-weight) daily and free access to pasture; and T4, feedlot (concentrate based on corn, alfalfa hay and soybean meal without access to pasture). At slaughter weight, samples of LD at the 11th rib were used for intramuscular lipid analysis. The diet was shown to be more important than breed in determining FA composition. Pasture beef had higher percentages of saturated fatty acids (SFA), n−3 polyunsaturated fatty acids (PUFA) and conjugated linoleic acid (CLA) and lower percentages of IMF, monounsaturated fatty acids (MUFA), n−6 PUFA and n−6/n−3 ratios than feedlot beef. HA beef presented lower percentages of SFA and more MUFA with a higher n−6/n−3 ratio than A and CHA×A. Comparing grass and feedlot beef the amounts of FA in muscle (mg/100 g) were, respectively 18:3 n−3 (44 vs. 11 mg), CLA (20 vs. 12 mg), 20:5 n−3 (20 vs. 11 mg), 22:5 n−5 (20 vs. 11 mg), 22:6 n−3 (12 vs. 6 mg) and n−3 PUFA (84 vs. 32 mg). Feedlot beef has more SFA (1372 vs. 1081 mg), MUFA (1574 vs. 1078 mg), PUFA (350 vs. 227 mg) and n−6 PUFA (318 vs.143 mg).